MODEL PEMBELAJARAN DI SEKOLAH DASAR 02 ASTRA KSETRA LAMPUNG DI MASA PANDEMI COVID-19: STUDI KOMPARASI ANTARA DARING DAN LURING [LEARNING MODEL IN THE ELEMENTARY SCHOOL 02 ASTRA KSETRA LAMPUNG IN THE COVID-19 PANDEMIC: A COMPARISON STUDY BETWEEN ONLINE AND OFFLINE] - Murti Muninggar; Hendrik Ahmad Syafrudin (Perkumpulan Ahli Bimbingan Konseling Islam Indonesia, 2021)
This study aims to: (1) Implement the concept of luring and online learning in The Elementary School 02 Astra Ksetra Lampung; (2) Reveal how the changes that occur in the offline learning system become online in The Elementary School 02 Astra Ksetra Lampung due to COVID-19; and (3) Explore how to implement online learning at The Elementary School 02 Astra Ksetra Lampung. This research used qualitative method with descriptive analysis research. Data analysis techniques use data reduction, data presentation, and draw conclusions. The results of this study indicate that: (1) In The Elementary School 02 Astra Ksetra Lampung on the concept of offline and online learning has a difference felt by students, because these students prefer offline learning (face-to-face), so in elementary school decided to combine offline learning and online learning; (2) Changes that occur in the offline learning system becoming online is a teacher using communication technology media for learning activities such as laptops and cellphones with media tools such as: Zoom, WhatsApp Group, and Rumah Belajar; and (3) Online learning implementation, still less effective, because in The Elementary School 02 Astra Ksetra Lampung there are still some children who do not have a communication technology tool in the process of learning activities. This makes the teacher to stay come to the house of students with members material fish and tasks that have been made by the teacher.